Ð˜ÑÐ¿Ð¾Ð»ÑŒÐ·Ð¾Ð²Ð°Ð½Ð¸Ðµ Ð¿ÐµÑ€Ñ„Ñ‚Ð¾Ñ€Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÑƒÐ³Ð»ÐµÐ²Ð¾Ð´Ð¾Ñ€Ð¾Ð´Ð¾Ð² Ð´Ð»Ñ Ð½Ð¸Ð·ÐºÐ¾Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð½Ð¾Ð³Ð¾ Ñ…Ñ€Ð°Ð½ÐµÐ½Ð¸Ñ ÑÐ¿ÐµÑ€Ð¼Ð¸ÐµÐ² Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Cherkashina, I. V.; Kuchkov, I. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The possibility of application of gas-transport blood substitute perfluorin (PF) as the component of cryoprotective medium for hypothermal storage of human spermatozoa has been investigated. The processes of lactic acid accumulation and cell motility have been studied the ability to change the type of metabolic processes in spermatozoa under perfluorin was concluded. The significant antioxidative effect of emulsion has been established. There was the suppression of diene and triene conjugates accumulation, reduction of malone dialdehyde concentration, and increase of superoxide dismutase activity. It has been shown that the suppression of developmental processes of lipid peroxidation by temperature factor in combination with antioxidative effect of perfluorin (as emulsion) increases the antioxidative activity of system.